2020
DOI: 10.1038/s41598-020-68195-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and transgenerational phenotypic, transcriptional and metabolic effects in rabbit males born following vitrified embryo transfer

Abstract: The advent of assisted reproductive technologies (ART) in mammals involved an extraordinary change in the environment where the beginning of a new organism takes place. Under in vitro conditions, in which ART is currently being performed, it likely fails to mimic optimal in vivo conditions. This suboptimal environment could mediate in the natural developmental trajectory of the embryo, inducing lasting effects until later life stages that may be inherited by subsequent generations (transgenerational effects). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 87 publications
2
25
0
Order By: Relevance
“…Previous studies have used animal models to explore the short-term effects in offspring conceived by IVF-FET. In a rabbit model, the offspring generated by cryopreservation embryo transfer exhibited impaired body growth during the observation time ( Garcia-Dominguez et al, 2020 ). Another study observed increased bodyweight in senescent mice born from cryopreserved embryos ( Dulioust et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used animal models to explore the short-term effects in offspring conceived by IVF-FET. In a rabbit model, the offspring generated by cryopreservation embryo transfer exhibited impaired body growth during the observation time ( Garcia-Dominguez et al, 2020 ). Another study observed increased bodyweight in senescent mice born from cryopreserved embryos ( Dulioust et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although rederived populations from cryopreserved embryos have some advantages, by optimising experimental facilities and reducing genetic drift this rederivation procedure could also contribute to distorting the control population [ 24 , 25 ]. Recently, García-Domínguez et al [ 51 ] compared naturally conceived animals with progeny generated after embryo cryopreservation, observing transgenerational effects in differentially expressed transcripts and metabolites in hepatic tissue that could be associated with a lower adult weight of the rederived population. Another effect to take into account would be the differential storage time, although these studies were performed to analyse the effect on post-thaw embryo survival and pregnancy outcomes, but not on the liveborn development [ 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the gene expression in preimplantation embryos [ 6 , 7 , 8 , 26 ], the foetal and placental weights [ 8 ], the foetal placental transcriptome and proteome [ 7 , 8 ], the skewed sex ratio [ 27 ], the offspring’s growth pattern and adult body weight [ 11 , 27 , 28 ] and the reproductive traits derived from females [ 11 , 29 ] and males [ 11 ]. More recently, we demonstrated the transgenerational effects following a vitrified embryo transfer procedure [ 30 ]. Taken together, these data showed transgenerational phenotypic changes in response to vitrification.…”
Section: Introductionmentioning
confidence: 99%